PENGARUH TINGKAT PARTISIPASI ANGKATAN KERJA, KUALITAS PENDUDUK, DAN TINGKAT PENGANGGURAN TERBUKA TERHADAP PERTUMBUHAN EKONOMI DI PROVINSI SUMATERA UTARA - Safrina, Yuni; Ratna, Ratna (LPPM UNIMAL, 2023)
This study aims to analyze the influence of the Labor Force Participation Rate, population quality, and the level of open response to economic growth in North Sumatra Province. This research uses secondary data from 2017-2021. The model used is the panel data regression model with three types of estimation, namely the commond effect model, the fixed effect model and the random effect model. To determine which model is best for use in the test through three tests Chow test, Hausmant test and LM test. Based on the test results that have been carried out, the selected model is the fixed effect model. The partial results show that the Variable Labor Force Participation Rate has a positive and significant effect on economic growth in North Sumatra, while the quality of the population and the level of open response have a negative and significant effect on economic growth in North Sumatra and together (simultaneously) the labor force participation rate. population quality, and the level of open damping have a positive effect on economic growth in North Sumatra Province. As well as the test results for the coefficient of determination obtained by the R Square value showing a value of 0.351 or 35.1% indicating that the ability of the independent variable to explain the effect on the dependent variable and the remaining 64.9% can be explained by other variables outside the research variables. Recommendations for the election of the government of North Sumatra can provide training to job seekers so that they have skills, and the government has achievements in opening jobs so that it will reduce action and can increase economic growth.